Influence of Electric Field on the Orientation of Ferroelectric Liquid Crystals inside micro capillaries - Budaszewski, Daniel; Domański, Andrzej W; Woliński, Tomasz R (Photonics Letters of Poland, 2013)
In the paper we present recent results on investigation of ferroelectric liquid crystals molecules orientation inside photonic crystal fibers, which consist of a set of micro capillaries. We have infiltrated glass micro capillaries with different inner diameters with the experimental ferroelectric liquid crystal mixture W-206K. The orientation of the liquid crystal molecules was controlled by the external electric field applied to the sample. We have obtained promising results about the orientation of the ferroelectric liquid crystal molecules and their behavior under influence of applied external electric field. The presented results may lead to design a new class of fast-switching fiber optic sensors. Full Text: PDF References P. St.J. Russell, "Photonic-Crystal Fibers", J. Lightwave Technol. 24, 4729-4749 (2006). CrossRef T. Larsen, A. Bjarklev, D. Hermann, and J. Broeng, "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Express 11, 2589-2596 (2003). CrossRef T. R. Wolinski, K. Szaniawska, K. Bondarczuk, P. Lesiak, A.W. Domanski, R. Dabrowski, E. Nowinowski-Kruszelnicki, J. Wojcik, "Propagation properties of photonic crystal fibers filled with nematic liquid crystals", Opto-Electronics Rev. 13(2), 177-182 (2005). DirectLink M.W. Haakestad, et al., "Electrically tunable photonic bandgap guidance in a liquid-crystal-filled photonic crystal fiber", IEEE Photon. Technol. Lett. 17, 819–821 (2005). CrossRef Matuszczyk M. "Structures and Properties of Ferroelectric Liquid Crystal Displays", Goteborg, Sweden, Chalmers Reproservice (1996). Q. Guo, E. P. Pozhidaev, A. K. Srivastava, Y. Ma, X. Wang, V. G. Chigrinov, H. S. Kwok, "Deformed Helix Ferroelectric Display with Low Driving Voltage and Fast Response Time", SID Symposium Digest of Technical Papers, Vol. 43 (1), 449-451, (2012). CrossRef E. P. Pozhidaev et al., "High Frequency Low Voltage Shock-Free Ferroelectric Liquid Crystal: A New Electro-Optical Mode with Electrically Suppressed Helix", Proc. of 31-th International Display Research Conference EuroDisplay 2011, Bordeaux-Arcachon, France, September 19-22 (2011). DirectLink Vladimir Chigrinov, Eugene Pozhidaev, Abhishek Srivastava, Guo Qi, Ma Ying, Hoi Sing Kwok, "Fast Ferroelectric Liquid Crystal Modes Based on Photoaligning Technology", SID 2013, Vancouver, Canada, May 2013 Clark, N. A. and S. T. Lagerwall, "Submicrosecond bistable electro-optic switching in liquid crystals", Appl. Phys. Lett. Vol. 36, 899-901(1980). CrossRef S. Mathews, Y. Semenova, G. Rajan, G. Farrell, "Tunable properties of Liquid Crystal filled Photonic Crystal Fibers", Proc. SPIE 7316, 73161E (2009). CrossRef D. Budaszewski, T.R. Woliński, M. A. Geday, J. M. Otón, "Photonic Crystal Fibers infiltrated with Ferroelectric Liquid Crystals", Phot. Lett. Poland 2(3) (2010). CrossRef